A review on factors that affect surface charge accumulation and charge-induced surface flashover. (6th April 2021) - Yuan, Mengqiang; Zou, Liang; Li, Zongze; Pang, Long; Zhao, Tong; Zhang, Li; Zhou, Jierui; Xiao, Peng; Akram, Shakeel; Wang, Zezhong; He, Shun
Abstract: The surface charge accumulation is very likely to trigger the surface flashover, which limits the large-scale application of DC GIL/GIS. This article comprehensively reviews the effect of six factors, including insulator-electrode shape, surface roughness of the insulator and conductor, metal particles, temperature, humidity, and gas type, on the insulator surface charging property. Furthermore, three models i.e. 'analogous ineffective region' expansion model, charge cluster triggered surface flashover model, and synergistic model of adsorbed gas, revealing the mechanism of charge triggered surface flashover phenomenon are reviewed and discussed. Future work from the perspective of theoretical analysis and engineering application are suggested in this field.